N-linked glycosylation is fundamentally linked to the surface expression of neuroligins - Cast, Thomas, author; Chanda, Soham, advisor; DeLuca, Jennifer, committee member; Di Pietro, Santiago, committee member; Tobet, Stuart, committee member (Colorado State University. Libraries, 2023)
N-linked glycosylation is one of the most prevalent forms of post-translational modification, decorating secreted and cell-surface transmembrane proteins as they are trafficked along the secretory pathway. While well-characterized in most tissues, non-canonical N-glycan diversification has been reported to occur in the central nervous system. Chapter 2 of this dissertation describes the importance of N-linked glycosylation for the neuroligin family of synaptic cell-adhesion molecules (NLGN1-4). NLGNs play a crucial role in regulating synaptic transmission strength by recruiting neurotransmitter receptors to synapses. Mutation of N-glycosylated residues increased retention of each NLGN isoform in the endoplasmic reticulum (ER), consequentially reducing their ability to interact with presynapses. Pharmacological inhibition of various stages of the N-glycan maturation pathway further revealed that only the initial transfer of the polysaccharide is essential for the surface expression of NLGN proteins. Chapter 3 characterizes a missense mutation identified in the NLGN4 gene of a patient with autism. This mutation, p.Arg101Gln (R101Q), is directly upstream of a conserved N-linked glycosylation site, which played a universal role for the surface localization of each NLGN isoform. Biochemical and cellular analysis revealed the NLGN4-R101Q variant to be immaturely glycosylated and mistrafficked, retained in the ER similarly to N-glycan site mutants. In neurons, the mistrafficked R101Q variant failed to reproduce the excitatory synaptogenic effects of NLGN4-WT, indicating an overall loss-of-function phenotype. Further, equivalent RQ mutations introduced in other NLGN isoforms mimicked the glycoprotein maturation and surface expression defects. Together, these findings reveal a profound overall significance of N-glycans for NLGNs and the conserved role of a specific N-linked glycosylation site for promoting the forward trafficking of NLGN protein.
Keywords: glycosylation; neuroligin; trafficking; N-linked; autism; synapse